2021 IEEE 48th Photovoltaic Specialists Conference (PVSC) 2021
DOI: 10.1109/pvsc43889.2021.9518799
|View full text |Cite
|
Sign up to set email alerts
|

Single-Source Pulsed Laser Deposition of MAPbI3

Abstract: As the employment of halide perovskite films in single-junction and tandem solar cells continues to soar, there is a strong drive -from academia to industry-to produce these films using dry processes, avoiding the use of toxic solvents. Vapor deposition methods such as co-evaporation have shown advantages of solvent-free approaches to produce high-efficiency solar cells. However, co-evaporation requires the use of multiple sources that challenge the deposition rate control of complex halide perovskite composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
(38 reference statements)
2
12
0
Order By: Relevance
“…The reported error represents the 95% confidence interval (CI) of the data. The evaporation rates (Å pulse À1 ) observed here approach those found in the literature for halide perovskites deposited by PLD at 0.55 Å pulse À1 for MAPbI 3 , [34] 0.5 Å pulse À1 for CsSnI 3 , [43] and 0.21 Å pulse À1 for Cs 2 AgBiBr 6 . [44] By increasing the number of pulses, which is easily controlled, we are able to grow thick films of perovskites.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The reported error represents the 95% confidence interval (CI) of the data. The evaporation rates (Å pulse À1 ) observed here approach those found in the literature for halide perovskites deposited by PLD at 0.55 Å pulse À1 for MAPbI 3 , [34] 0.5 Å pulse À1 for CsSnI 3 , [43] and 0.21 Å pulse À1 for Cs 2 AgBiBr 6 . [44] By increasing the number of pulses, which is easily controlled, we are able to grow thick films of perovskites.…”
Section: Resultssupporting
confidence: 84%
“…Similarly, Tai et al [33] used a laser-induced flash-evaporation process yielding 16.8% efficient devices and parallel advances in pulsed laser deposition reported 14% efficient devices with a MA x FA 1Àx PbI 3 composition, demonstrating the transfer of multiple organic cations as a single-source. [34,35] However, the lasers involved in such deposition systems can be cost-prohibitive for deployment in large-scale, such as those needed for PV.…”
Section: Doi: 101002/adem202400636mentioning
confidence: 99%
“…Non-stoichiometric ratios of the inorganic to the organic components (PbI 2 /PbCl 2 : MAI/FAI = 1:8) were used as determined in previous work. 11 The mol ratio of the organic components MAI: FAI was chosen as 75:25 as optimized in a previous work. 12 The PbCl 2 content in the target was varied from 0-50 mol% with respect to PbI as received, were transferred to zirconia-coated vials containing zirconia beds and mixed using a housebuilt rotatory ball miller.…”
Section: Methodsmentioning
confidence: 99%
“…This journal is © The Royal Society of Chemistry 2024 one source, given the inevitable decomposition of the organic halides at the elevated temperatures required to simultaneously deposit the inorganic compounds. While alternative single-source techniques such as laser deposition or sputtering were proposed, 44,82,83 they were not able to fully leave the ''comfort zone'' either because of lower performance or only limited improvements in deposition speed and proof of their suitability in an industrial setting is yet to be demonstrated. Classical multisource co-evaporation approaches, which are the most successful approaches when it comes to versatility and performance on a laboratory scale, do not offer much room for improvements either (other than geometrical source considerations discussed before), as they are similarly limited by the maximum accessible deposition rate of the organic compounds.…”
Section: Throughputmentioning
confidence: 99%